Prevalence of low back ache and disability among the elderly patients attending tertiary care hospital in Andhra Pradesh: a cross-sectional analytical study - Sathiyamoorthi, Sathiyanarayanan; Aravindhakshan, Rajeev; Veesam, Anantha Prakash; A., Jeganish (International Journal Of Community Medicine And Public Health, 2025)
Background: Low back pain (LBP) is seen in about 600 million people worldwide. The purpose of the study was to determine the prevalence of LBP and disability among elderly patients. Methods: This cross-sectional study was conducted at AIIMS, Mangalagiri. A semi-structured interview schedule including sociodemographic details, and the Oswestry low back pain disability questionnaire was used for data collection. Descriptive variables were described as mean±standard deviation, Chi-square and Fisher’s exact tests were used to assess associations between variables. Results: A total of 358 patients participated in the study, and the prevalence of LBP was found to be 61.5% which was higher among females than males. There was moderate disability in 46.4%, and severe disability in 34.5% of our study population. Conclusions: This study adds to the epidemiological evidence that reveals a high prevalence of LBP and disability among elderly patients. Identified risk factors in this study may also reinforce the importance of setting different interventions and preventive measures to reduce lower back pain risk.